Composição específica, análise morfométrica e contaminação por metais em nadadeiras de tubarões comercializados no polo pesqueiro do município de Raposa-MA - COELHO, Alline Vieira (2022)
The excessive capture of elasmobranchs in the world is also driven by the international fin trade very high commercial value. This practice called "finning", which includesthe constant removal of fins, is one of the causes of the great decline in shark populations. The research aims to identify the species of sharks from the dorsal and pectoral fins removed for commercialization in the municipality of Raposa - MA. In addition to identifying the species of sharks landed in the fishing pole of the municipality, it was intended to evaluate the variability of fins over time as an indication of the presence/absence of species in the coastal region of the state, to analyze the morphometry of the fins of different species, and identify the species through the image of the fins using the iSharkFin software, and finally, determine the levels of contaminating metals in these commercialized fins. Shark fins were obtained from fishermen/marketers. The sampling of the fins was performed by identifying the sets (dorsal and pectoral pair) and random sets (when there is no pair) for morphometric analysis. Thus, 13 species of sharks were identified, among them, six are from occurrences close to the fishing pole of the municipality of Raposa-MA: Galeocerdo cuvier, Prionace glauca, Alopias superciliosus, Sphyrna mokarran, Carcharhinus plumbeus and Carcharhinus longimanus. And two species were identified using pectoral fins: Sphyrna mokarran and Lamna nasus. An excellent alternative could also be a mobile version, allowing for a more active and present inspection. The bioaccumulation of toxic metalsin the pectoral and dorsal fins of sharks sold in the fishing pole of Raposa-MA highlighted the need for concern about human health in view of the results of some metals such as chromium (Cr), zinc (Zn), lead (Pb ), mercury (Hg) and arsenic (As). higher than the maximum daily limits acceptable by the food safety agencies ANVISA (National Health Surveillance Agency) and CODEX ALIMENTARIUS